Analisis Kebijakan Standar Pembiayaan Pendidikan Guru Sekolah Dasar - Liska Ulandari Ulandari; Ar Ridha Ridha; Dina Rozalita Rozalita; Rizki Ananda Ananda; Ramdhan Witarsa Witarsa (Universitas Negeri Makassar, 2022)
This study aims to describe the standard policy of financing primary school teacher education. This research method uses qualitative research methods with a literature review approach. The research stages were carried out starting from article collection, article reduction, article display, discussion, and conclusion. Sources of research data are articles from accredited national journals in the last 10 years (2013-2022). The results showed that from 14 articles, 4 articles were obtained that matched the title topic. Funding standards for primary school teacher education need to pay attention to the stages of financing management, especially during the planning and realization of financing. The principle of facility utilization needs to be considered for efficiency in the use of learning facilities in primary school teacher education in order to achieve learning objectives and improve the quality of primary school teacher education. Primary school teacher education managers need to find other sources of funding so that the infrastructure and facilities for primary school teacher education are more sophisticated and can facilitate students to develop their competencies based on field needs